Scientific Opinion on the safety assessment of the substance ethylene glycol dipalmitate, CAS No 624‐03‐3, for use in food contact materials. (18th February 2015) - ,; ,
Abstract: This scientific opinion of the EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF Panel) deals with the safety assessment of ethylene glycol dipalmitate (EGDP), CAS No 624‐03‐3, FCM substance No 01048, for use as a processing aid at concentrations of up to 2 % in various types of plastics, acting as a lubricant to improve injection moulding and to improve the distribution of additives in the polymer melt. Based on the modelled specific migration results, it cannot be ruled out that the overall migration limit may be exceeded. No toxicological data were provided for the substance EGDP. Toxicological data from similar ethylene and propylene glycol fatty acid esters were submitted for "read across". Based on the genotoxicity data provided, the CEF Panel considered that there is no indication of genotoxic potential for the substance EGDP. Based on two 90‐day oral toxicity studies on structural homologues, no sub‐chronic toxicity of EGDP is expected at relevant doses (< 1 000 mg/kg bw/day). The CEF Panel concluded that the substance EGDP is not of safety concern for consumers if it is used in plastics intended for contact with all types of foodstuffs under all contact conditions, provided that the fatty acid precursor is obtained from edible fats or oils using conventionally applied procedures, and that any impurities in the ethylene glycol are under the control of the producer. The substance should be included in the group total specific migration limit (SML(T)) of 30 mg/kg expressed as ethylene glycol.